Draft genome sequence of the coccolithovirus EhV-84. Issue 1 (July 2011) - Nissimov, Jozef; Worthy, Charlotte; Rooks, Paul; Napier, Johnathan; Kimmance, Susan; Henn, Matthew; Ogata, Hiroyuki; Allen, Michael
Abstract TheCoccolithoviridae is a recently discovered group of viruses that infect the marine coccolithophoridEmiliania huxleyi . Emiliania huxleyi virus 84 (EhV-84) has a 160–180 nm diameter icosahedral structure and a genome of approximately 400 kbp. Here we describe the structural and genomic features of this virus, together with a near complete draft genome sequence (∼99%) and its annotation. This is the fourth genome sequence of a member of the coccolithovirus family.